Configuration and expansion of secondary level and teacher training (higher level) in Tierra del Fuego AeIAS (1991-2006). A comparative analysis of two investigations (Praxis Educativa, 2024)
This article aims to analyze the relationships between the configuration and expansion of the secondary level, and the initial teacher training for that level in Tierra del Fuego A.e.I.A.S, (1991-2006). This is a comparative study of two investigations: one linked to the configuration of the secondary level in Tierra del Fuego, currently in progress (Paez et al., 2023), and the other to the configuration of the teacher training system since provincialization 1991- 2020 (Abendaño, 2022). Both are part of the line of research “Critical Factors in Education-Educational Policy”, of the Institute of Education and Knowledge of the National University of Tierra del Fuego. Methodologically, the method of constant comparison of the field and the results of both investigations were used. Among the main findings, differential expansive processes were identified at each level, crossed by common events, but poorly articulated from the policies.
Keywords: Expansion - configuration - - secondary level - teacher training policies (initial) - articulation between levels.